HAK DAN KEWAJIBAN PARA PIHAK DALAM TRANSAKSI JUAL BELI ONLINE - Indah Puspita, Made; -, Adiwati (Kertha Semaya : Journal Ilmu Hukum, 2014)
This paper, entitled 'Rights and Obligations of the Parties to the Sale and Purchase Transactions Online. This paper aims to find out anything what rights and obligations of consumers and businessmen in doing online transaction. In the writing of normative legal research methods to approach legislation. The conclusion that can be drawn in this paper is the consumer's rights set out in article 4, consumer obligations stipulated in Article 5, the right of entrepreneurs set out in article 6, and the obligations of business operators governed by Article 7 of Law No. 8 of 1999 on Consumer Protection.
Keywords: Rights, Obligations, Consumer, Online